Prediksi Motivasi Kerja, Lingkungan Kerja, dan Kompensasi Finansial Terhadap Kinerja Karyawan - Komara, Edi; Al Giffari, Muhammad (STIE Indonesia Banking School, 2023)
The purpose of this study was to determine the effect of work motivation, work environment, and financial compensation on employee performance (Case Study of PT XYZ).The method used in this research is a method of collecting data through a questionnaire which is measured using a Likert scale diagram. The sampling method uses saturated sampling technique by using all employees into the population and getting the results of 47 respondents. This research is a quantitative study using an associative strategy with SEM-PLS calculations using SmartPLS Version 3.2.9 software.The results of this study state that Work Motivation, Work Environment has a positive and significant effect. Meanwhile, Financial Compensation has a negative and insignificant effect.